ANALISIS SPASIAL-TEMPORAL PERUBAHAN PENGGUNAAN LAHAN TERHADAP KENAIKAN SUHU BERBASIS GOOGLE EARTH ENGINE DI KABUPATEN LOMBOK BARAT (Studi Kasus: Kecamatan Labuapi, Kediri, dan Gerung) - Irma Yuliani; Uzlifatul Azmiyati; Lalu Auliya Aqraboe Littaqwa (Fakultas Teknik - Universitas Satya Negara Indonesia, 2026)
Land use changes have occurred in many areas, including West Lombok Regency, particularly in the districts of Labuapi, Kediri, and Gerung, where many rice fields have been converted into residential areas due to increasing human activity. This research aims to analyze the temperature increase resulting from these land use changes in the region. The methods used are a combination of quantitative and qualitative approaches, including land classification analysis (supervised classification) and Land Surface Temperature (LST) analysis. Data processing was carried out using Google Earth Engine, ArcGIS, and QGIS, with Landsat 8 imagery data used to classify land cover types. The analysis results indicate a temperature increase over the past 10 years. Based on the Pearson correlation test between land use and temperature increase, the significance value is 0.663 > 0.05. However, other factors such as heat production from vehicles, machinery, household activities, topography, wind circulation, and reduced vegetation also contribute to the temperature increase.